FROM DEMOCRATIC OPENING TO DEMOCRATIC BREAKTHROUGH: A STUDY OF DEMOCRATIC TRANSITION IN POST-COMMUNIST KAZAKHSTAN - Baghat, Muneer Ahmad; Firdous, Tabasum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As the Soviet Union's collapse loomed, many predicted chaos and ethnic strife in Central Asia. However, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan, the five republics, defied these expectations by swiftly establishing democratic institutions and market-driven economies. This successful transformation was largely due to the adept leadership in each republic, which skillfully navigated the challenges of the post-Soviet era and metamorphosed into advocates of democracy, fervently committing themselves to democratic values within their respective territories. Taking these factors into consideration, the paper aims to investigate the roots of democratic wave in Central Asia and to explore the democratic transition in Kazakhstan. To analyze any democratic transition in the post-Soviet era, it is essential to consider the historical context shaped by the rise of Mikhail Gorbachev in 1988. “Institutions do matter” and restructuring or formulating institutions shapes the country’s political development. Institutions such as, legislature, executive, political parties etc. are cornerstone for shaping and institutionalizing democratic political culture. While restructuring Political infrastructure in Kazakhstan, the study will focus on the role played by these institutions in facilitating democratic opening in Kazakhstan while emphasizing the transformative power of institutional dynamics.